Exploring the Use of Learners’ First Language in English as a Foreign Language Classroom - Cakrawati, Laxmi Mustika (International Journal of Education, 2019)
The use of learners’ first language has been debated for years. Some of the researchers think that using learners’ first language can be a help for foreign language learning while others argue that it can be hindrance. Therefore, this study focuses on investigating students’ and teachers perceptions on the use of learners’ first language (L1) and problems they encountered in using English in the English as a Foreign Language (EFL) classroom context. The study involved 150 students of grade X and grade XI and two English teachers in a high school in rural Karawang, West Java. The data were collected through questionnaire, interviews, and classroom observation and were analyzed using mixed methods approach. The findings of the study reveal that the participants showed various responses related to the use of L1. The result of the study indicates that the participants perceive L1 as facilitating learning tool that can help both teachers and students in learning process. Thus, it is suggested that teachers should be able to not only use L1 wisely but also encourage their students to use more English in the classroom.